(untitled) (International Seven Journal of Multidisciplinary, 2023)
The scarcity of water in the world makes the correct management of water resources increasingly important. Based on this dynamic, the work focused on the study of the chemical quality of three dams in the City of São Paulo Region. They are: Guarapiranga, Mairiporã and Billings. Where the analysis process was carried out by synchrotron radiation at the National Synchrotron Light Laboratory (LNLS). The results were promising, where 15 chemical elements were detected: Aluminum (Al), Silicon (Si), Phosphorus (P), Sulfur (S), Chlorine (Cl), Potassium (K), Calcium (Ca), Titanium (Ti ), Manganese (Mn), Iron (Fe), Bromine (Br), Strontium (Sr), Tin (Sn), Barium (Ba) and Cerium (Ce). Their values ​​were well below the limits called Maximum Permissible Values ​​(VMP) for human consumption. All in the order of microliters (μl). Emphasis on Iron, which had the highest concentration for the dams, but without damage to human health.